BALANCE SCORECARD IN COMPETITIVE STRATEGY - Aryan Danil Mirza. BR; Mira Apriliana Sari (TECHNOBIZ : International Journal of Business, 2025)
The purpose of this study is to explain how the implementation of the Balanced Scorecard can be used to improve business strategy, especially in companies implementing competitive strategies. The world of business and government have both adopted the BSC as a tool for measuring performance, but its implementation is not without challenges. One of these challenges is determining which perspective to highlight when building the relationship between performance and strategy. This study is qualitative and takes a literature-based approach. This study shows that competitive strategies take a slightly different approach by using the BSC model, and this is reflected in strategy formulation.